Finance and Development, December 2006. (Finance and Development; Finance and Development ;, 2006)
'Africa: Making Its Move' explores some of the obstacles facing sub-Saharan Africa as it attempts to capitalize on changes that offer fresh opportunities for growth and poverty reduction. The lead article describes the changes and suggests how Africa can build on them to progress further. Other articles focus on the aid situation, financial sector development, trade, the business environment, and political and policy reform on the continent. 'Country Focus' examines the Central African Economic and Monetary Community, and two guest contributors look at how the international community can help the most fragile states and how oil-producing countries can manage windfall revenues. 'People in Economics' profiles the European Central bank's first chief economist, Otmar Issing; 'Picture This' examines the global housing slowdown; and 'Back to Basics,' explains current account deficits. Another article discusses the realities of health financing.